2017
DOI: 10.1111/jcmm.13165
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of human villous trophoblasts preserves cardiac function in mice with acute myocardial infarction

Abstract: Over the past decade, cell therapies have provided promising strategies for the treatment of ischaemic cardiomyopathy. Particularly, the beneficial effects of stem cells, including bone marrow stem cells (BMSCs), endothelial progenitor cells (EPCs), mesenchymal stem cells (MSCs), embryonic stem cells (ESCs), and induced pluripotent stem cells (iPSCs), have been demonstrated by substantial preclinical and clinical studies. Nevertheless stem cell therapy is not always safe and effective. Hence, there is an urgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Myoblast fusion in myogenesis is energy-dependent and enhanced by creatine treatment in a creatine kinase-dependent manner 47 , lending support to the idea that STB differentiation is also an energy-demanding process modulated by the GCM1-CKMT1 axis. Human and mouse trophoblasts with cardiac repair capacity have recently been demonstrated in a mouse model of myocardial infarction (MI) 48 , 49 . It is intriguing to test the capacity of TS Term cells in repair of damaged cardiomyocytes in MI mice.…”
Section: Discussionmentioning
confidence: 99%
“…Myoblast fusion in myogenesis is energy-dependent and enhanced by creatine treatment in a creatine kinase-dependent manner 47 , lending support to the idea that STB differentiation is also an energy-demanding process modulated by the GCM1-CKMT1 axis. Human and mouse trophoblasts with cardiac repair capacity have recently been demonstrated in a mouse model of myocardial infarction (MI) 48 , 49 . It is intriguing to test the capacity of TS Term cells in repair of damaged cardiomyocytes in MI mice.…”
Section: Discussionmentioning
confidence: 99%
“…ASCs‐based therapy is a rapidly evolving field for diseases without effective treatments, and during the past decade, strong evidence has been accumulated including pre‐clinical and clinical trials ranging from proof‐of‐concept to phase II trials . As an alternative source of human stem cells, the newly identified MenSCs exhibit their potential for ASC‐based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrated that BMMC combined with anti-inflammatory nanoparticles result in great potential for regenerative medicine. Many results have indicated that cell injection into a myocardial infarction model has resulted in some improvement in cardiac function [ 16 , 17 ]. We examined via an echocardiography study the effects of treatment four weeks post-implantation; some data have shown that BMMC combined with anti-inflammatory nanoparticles recover diastolic and systolic function, and improve the function ejection fraction in the BMMC+15d-PGJ2 group in the infarcted region.…”
Section: Discussionmentioning
confidence: 99%